Pseudoparabolic variational inequalities without initial conditions - Lavrenyuk, S. P.; Ptashnik, M. B. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider a pseudoparabolic variational inequality in a cylindrical domain semibounded in a variable t. Under certain conditions imposed on the coefficients of the inequality, we prove theorems on the unique existence of a solution for a class of functions with exponential growth as t → ∞.